Comparative study of clinico-biochemical profile and outcome of acute kidney injury in outborn and inborn neonates - Kumar, Nayan; Karnawat, B. S.; Badaya, Navneet (International Journal of Contemporary Pediatrics, 2018)
Background: Acute Kidney Injury (AKI) is one of the major clinical problem in hospitalised neonates having variable outcomes. Prognosis depends on early diagnosis, associated risk factors and type of renal failure. The present study was undertaken to evaluate and compare risk factors, biochemical derangements and outcome of AKI in outborn and inborn neonates. Methods: For this hospital based prospective study 100 neonates were enrolled who were admitted in the NICU, diagnosed as AKI who had serum creatinine >1.5mg/dl. Study was done for 1 year from June 2016 onwards. Results: A large majority (72.3%) cases were outborn neonates (extramural) whereas (27.7%) cases were inborn neonates (intramural). Most of (79.8%) cases were term and were admitted during summer months. In outborn, type of AKI in descending order was prerenal (64.7%), renal (33.8%) and postrenal (1.5%) while in inborn neonates, cases were equally (50%) divided in between renal and prerenal. Among outborn neonates risk factors for AKI was dehydration (44%), sepsis (28%) and shock (16%) whereas in inborn, perinatal asphyxia (31%), dehydration (27%), shock (23%) and sepsis (11.5%) were risk factors. In outborn 36.8% cases were oliguric whereas in inborn 53.9% cases were oliguric. Conclusions: The maximum cases of AKI were outborn neonates in which outborn dehydration was the commonest cause while in inborn neonates perinatal asphyxia was the commonest cause. Sepsis and shock were other causes in both groups. Presence of oliguria, intrinsic AKI and shock carried poor prognosis.